A Review of Approaches to Construct Social Discount Rate (Sains Humanika, 2016)
There is increasing concern on how public projects are being evaluated especially for public projects that bring impacts towards the economic, social and environmental of the nation in the long-term, for example infrastructural, environmental protection, energy efficiency, healthcare, education expenditures and others. Thus, the federal government and state government recommend project assessors to adopt cost-benefit analysis for major infrastructure and social investment as well as for regulatory initiatives. Cost benefit analysis has been widely used as a tool to enable stakeholders to make a better decision for projects by systematically comparing the social costs and benefits with the emphasis on valuing them in monetary term. One of the most significant parameters for cost benefit analysis is the social discount rate. It is a rate that used to convert the future social costs and benefits into present value. However, there is a long-time debate on how to construct appropriate social discount rate. Literature reveals that there are various popular approaches to construct social discount rate, such as Social Time Preference (STP) approach, Social Opportunity Cost of Capital (SOC), and Shadow Price of Capital (SPC). The selection of approaches is a significant process to construct an appropriate social discount rate for the project. In this paper, author examines theoretical for each approach and procedures to construct social discount rate. A framework will be developed to guide the assessor in selecting the approaches to construct social discount rate. This paper intends to review social discount rate construction approaches and the pros and cons of each approach. The paper would provide insight to assessor in selecting the approach in construction social discount rate.Â
Keywords: Social discount rate; social time preference; social opportunity cost of capital and shadow price of capital.